2020
DOI: 10.1142/s0192415x20500780
|View full text |Cite
|
Sign up to set email alerts
|

Positive Role of Chinese Herbal Medicine in Cancer Immune Regulation

Abstract: Complementary and alternative medicine (CAM) plays a critical role in treating cancer patients. Traditional Chinese Medicine (TCM) is the main component of CAM. TCM, especially Chinese Herbal Medicine (CHM), has been increasingly used in China, some other Asian countries and European countries. It has been proven to enhance the efficacy of chemotherapy, radiotherapy, targeted-therapy, and immunotherapy. It lessens the damage caused by these therapies. CHM functions on cancer by inhibiting tumor progression and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
74
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(94 citation statements)
references
References 76 publications
4
74
0
Order By: Relevance
“…In this study, the majority of participants reported the same purpose before (69.7%) / after (71.8%) the epidemic of COVID-19, as immune system has a close interaction with COVID-19 infection and cancer progression [22,23]. CAM was quite famous for its regulating immune system effect in cancer patients and fighting against COVID-19 [24,25], and cancer patients seemed to show more interest (70.2%) and confidence (79.4%) in CAM treatment during the COVID-19 though their frequency of CAM clinic visit dropped significantly.…”
Section: Discussionmentioning
confidence: 65%
“…In this study, the majority of participants reported the same purpose before (69.7%) / after (71.8%) the epidemic of COVID-19, as immune system has a close interaction with COVID-19 infection and cancer progression [22,23]. CAM was quite famous for its regulating immune system effect in cancer patients and fighting against COVID-19 [24,25], and cancer patients seemed to show more interest (70.2%) and confidence (79.4%) in CAM treatment during the COVID-19 though their frequency of CAM clinic visit dropped significantly.…”
Section: Discussionmentioning
confidence: 65%
“…In the first study [30], there is significant improvement in chest discomfort, fullness and distension and shortness of breath, but not for palpitations and pain. Moreover, other authors consider the use of traditional Chinese medicine in the decrease of side effects caused by cancer treatments such as chemotherapy or radiotherapy [49]. In the second [39], there is a greater reduction in perioperative anxiety in both intervention groups, but not in the other factors to be studied.…”
Section: Discussionmentioning
confidence: 99%
“…The same as below. 10 Oxidative Medicine and Cellular Longevity the concentration of serum CCL4 showed a marked decline in the G+F group, compared with the control group (Figure 3(g)). These results confirmed that MDSCs were one of the critical cell populations for the FZQX prescription to prevent the recurrence and metastasis of lung cancer.…”
Section: Mdscs Played a Key Role In The Inhibition Of Tumormentioning
confidence: 94%
“…In addition to surgery and chemotherapy, most Chinese patients seek help from traditional Chinese medicine (TCM) during or after standard first-line therapy. Numerous clinical trials have proved that TCM has its advantages in antitumors [ 9 , 10 ]. The effects of TCM in alleviating symptoms, reducing side-effects, and improving quality of life and adverse events caused by chemotherapy have been confirmed [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%